POST-WAR DEVELOPMENT OF PUBLIC TRANSPORT IN THE CONTEXT OF THE «RECONSTRUCTION PLAN OF UKRAINE» - ZAKHAROV, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article provides a detailed analysis of the post-war development of public transport in Ukraine in the context of the 2022 document «Ukraine Recovery Plan», more precisely - one of its headings – «Recovery and development of infrastructure». The article emphasizes that the current state of transport enterprises indicates that the "old" problems of public transport have remained relevant, the "new" ones have turned out to be even more significant and require not only a review of the entire existing transport system of the country, the transport system of every city where there is an urban public transport, as well as even greater capital investments for the restoration of the road infrastructure, rolling stock and transport infrastructure of our cities destroyed by military aggression. Key challenges in this area, key opportunities, main obstacles and limitations are described in detail. The most important task now is to create conditions for maintaining the transport infrastructure in proper condition, increasing the capacity of checkpoints, reorientation of cargo transportation. In addition, the issues of integration of the transport network of Ukraine into the EU transport network have not been removed from the agenda. For this, it is necessary to carry out appropriate measures and adopt a number of regulatory and legal acts. Therefore, the goal of the «Ukraine Recovery Plan», which we analyzed in this article, is "to ensure the harmonization of regulatory and legal acts and organizational activities of the transport industry of Ukraine with EU countries to meet the needs of the population in transportation and ensure the development of the country's economy by changing approaches to the formation of transport -logistics solutions and development of modern transport infrastructure in accordance with EU standards". The purpose of the article is to analyze the current situation and directions of the post-war development of urban public transport in the context of the adopted «Ukraine Recovery Plan».
Keywords: urban public transport; road management; transport infrastructure; rolling stock; transport system of cities